Production of recombinant HIV monoclonal antibodies for human health in transgenic maize seeds - Ramessar K.; Stoger E.; Capell T.; Christou P. (Cereal science and technology for feeding ten billion people: genomics era and beyond, 2008)
Monoclonal antibodies are difficult to express in microbial expression systems due to their specific folding requirements and need for post-translational modifications. Plant production systems, apart from being inexpensive with potential for rapid, economical scale-up, have the necessary processing steps for folding and assembly (via the secretory pathway). Cereal seeds offer high stability of proteins when dry and can be easily stored for long periods of time. The objective of this study therefore, was to express the neutralizing HIV monoclonal antibody (C2G12) into the endosperm tissue of maize seeds. The heavy and light chain genes of C2G12 were cloned into suitable transformation vectors containing the rice glutelin-1 promoter for endosperm-specific expression. These genes, together with the bar gene for selection, were co-bombarded into immature zygotic M37W maize embryos (an elite South African variety) either as full vector constructs, or minimal transgene cassettes (promoter, open reading frame and terminator). Selection occurred on phospinothricin-containing media and independent transgenic events were accordingly identified and characterized by Southern blot analysis.
Meeting of the Eucarpia Cereal Section, 2006/11/13-17, Lleida (Spain)